Improving Early Mathematics Skills Through Contextual Theme-Based Smart Box Media in Early Childhood - Yuliani Waladani; Purwaningsih Purwaningsih; Uswatun Khasanah; Ismatul Khasanah; Ika Sukesmi (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This classroom action research aims to improve early mathematics skills of Group B children at TK Desa Majasto 02 through the implementation of a contextual theme-based